(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
It is critical that nursing assistants improve their skills immediately because of the delicate nature of their employment. Subsequently, the purpose of this study was to evaluate the impact of positive psychology training on the resilience and self-control of nursing assistants. This study used a quasi-experimental design with a control group receiving an assessment before, during, and after the intervention. There were a total of 64 nursing assistants employed in the city of ______ in 2022 and 2023; 32 of them were randomly chosen and split into two groups of 16. Our dependent variable was measured at three phases using the Self-Control Scale and the Connor-Davidson Resilience Scale. We used SPSS 26 and its repeated-measures analysis of variance and Bonferroni post hoc test to examine the data. According to the findings, the control group and the group that received positive psychology training differed significantly (p<0.01) in terms of self-control and resilience.It is suggested that hospitals use positive psychology training for nursing assistants because of how well it improves self-control and resilience.